Essai bibliographique sur l'archéologie francophone de la Mésoamérique = Bibliographical essay upon the French-speaking contributions to Mesoamerican archaeology = Ensayo bibliográfico sobre la arqueología francófona de Mesoamerica - Taladoire, Eric (Access archaeology., 2019)
This bibliography of contributions in French to Mesoamerican studies aims to: assess the existing situation; provide the most complete list of references and draw attention to unknown contributions; evaluate the contribution of the most recent formations; insist upon the necessary confrontation of methods and points of view.